Seeking Integrity in Teacher Education Transforming Student Teachers, Transforming My Self - Schulte, Ann Katherine (Self-Study of Teaching and Teacher Education Practices, 2009)
In this book, a teacher educator examines her practice as a way of learning about teaching as well as challenging teacher education. It is about how one teacher educator sought to transform the perspectives of her student teachers, in order to better prepare them to teach diverse populations of students, while challenging her own beliefs about how best to do that. The author seeks integrity in her practice, defined as her ability to enact what she teaches preservice teachers to do. This self-study contributes to understanding the broader question: How much can one affect and change the discourse within education when one also inhabits the characteristics that are privileged by the institution? The teacher education literature supports the need to study this type of self-reflection. This book offers a unique perspective on the analogous relationship involved when a teacher educator teaches teachers how to examine the impact of their own identities on their teaching while examining that herself.